New application of decaniobate salt as basic solid in the synthesis of 4H-pyrans by microwave assisted multicomponent reactions - Gutierrez, Luisa F. (2018)
This study focuses on the search of new applications of polyoxometalates known as decaniobate ions [Nb10O28]6−. The decaniobates can be used as basic solid catalysts in multicomponent reactions to obtain good yields to 4H-pyrans (> 95%) under microwave radiation and solvent-free conditions, using several aldehydes with different electron-withdrawing or electron donor substituents. The synthesis of (TMA)6 [Nb10O28]6H2O was performed following a simple protocol (HPNb), which was modified to decrease the number of hexaniobate species that are formed as impurities (HPNb-HF).